2007
DOI: 10.1017/s0025315407055956
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of meiofauna and free-living nematodes in hydrothermal vent mussel beds on the northern and southern East Pacific Rise

Abstract: The ecology and biogeography of meiofauna at deep-sea hydrothermal vents have historically received less attention than those of mega-and macrofauna. This study examines the composition of major meiofaunal taxa in beds of the mussel Bathymodiolus thermophilus at hydrothermal vents on the northern and southern East Pacific Rise (EPR) and presents the first comparison of species assemblages of the dominant taxon, the nematodes, among sites spanning 27 degrees of latitude. Meiofaunal samples were collected by sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 28 publications
(105 reference statements)
3
52
0
Order By: Relevance
“…In recent years, the deep-sea hydrothermal vent meiofauna has increasingly gained interest and several studies have been published (Vanreusel et al 1997;Tsurumi et al 2003;Zekely et al 2006a, b;Copley et al 2007;Gollner et al 2007Gollner et al , 2010bGollner et al , 2013Limén et al 2007;Degen et al 2012;Cuvelier et al 2014;Sarrazin et al 2015). Meiofauna is considered to contribute up to 20% of the total diversity known from deep-sea hydrothermal vents (Bright 2006).…”
Section: Meiofauna From Hydrothermal Ventsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the deep-sea hydrothermal vent meiofauna has increasingly gained interest and several studies have been published (Vanreusel et al 1997;Tsurumi et al 2003;Zekely et al 2006a, b;Copley et al 2007;Gollner et al 2007Gollner et al , 2010bGollner et al , 2013Limén et al 2007;Degen et al 2012;Cuvelier et al 2014;Sarrazin et al 2015). Meiofauna is considered to contribute up to 20% of the total diversity known from deep-sea hydrothermal vents (Bright 2006).…”
Section: Meiofauna From Hydrothermal Ventsmentioning
confidence: 99%
“…In the vicinity of deep-sea vents, meiofauna can be associated with habitats ranging from inactive bare basalts (Gollner et al 2010b) and sediments (Vanreusel et al 1997) to diffuse vent flow areas colonised by macrofaunal assemblages (Zekely et al 2006a, c;Sarrazin et al 2015). Almost all studies that include meiofauna were conducted along the East Pacific Rise (EPR; Dinet et al 1988;Flint et al 2006;Gollner et al 2006Gollner et al , 2007Gollner et al , 2010bZekely et al 2006a, b, c;Copley et al 2007;Limén et al 2007Limén et al , 2008, with the exception of four studies: two in the West Pacific back-arc basins (Shirayama 1992;Vanreusel et al 1997) and three on the Mid-Atlantic Ridge (MAR; Zekely et al 2006a, b, c;Cuvelier et al 2014;Sarrazin et al 2015). The picture emerging from these studies points to a vent meiofauna with low abundance and diversity (Dinet et al 1988;Vanreusel et al 1997;Tsurumi et al 2003;Copley et al 2007;Limén et al 2007;Gollner et al 2010b) compared with other chemosynthetic ecosystems characterised by less extreme conditions.…”
Section: Meiofauna From Hydrothermal Ventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst mega-and macrofauna in HVs have been studied since their discovery, the ecology of meiofaunal organisms has only recently been included in vent studies (Tsurumi et al 2003;Zekely et al 2006a, b;Limén et al 2007;Gollner et al 2007Gollner et al , 2010aCopley et al 2007;Sarrazin et al in press). Several HV habitats, from inactive bare basalts (Gollner et al 2010b) and sediments (Vanreusel et al 1997) to diffuse flow areas colonized by macrofaunal assemblages (Zekely et al 2006a, c), host meiofaunal communities characterized by low abundance and diversity, linked with the abiotic and biotic conditions of the habitat (Gollner et al 2010b;Zekely et al 2006a, c;Degen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A study on mussel beds of different ages (4 to >20 years) showed that nematodes were less abundant and diverse at younger sites (Copley et al 2007). Volcanic eruptions would negatively impact nematodes that may require long periods to colonize a newly lava-flooded area (Gollner et al 2013).…”
Section: Introductionmentioning
confidence: 99%